Institutional shocks and economic outcomes: Allende's election, Pinochet's coup and the Santiago stock market - Daniele Girardi; Samuel Bowles (University of Massachusetts, Department of Economics, 2017)
To study the effect of political and institutional changes on the economy, we look at share prices in the Santiago exchange during the tumultuous political events that characterized Chile in the early 1970s. We use a transparent empirical strategy, deploying previously unused daily data and exploiting two largely unexpected shocks which involved substantial variation in policies and institutions, providing a rare natural experiment. Allende's election and subsequent socialist experiment decreased share values, while the military coup and dictatorship that replaced him boosted them, in both cases by magnitudes unprecedented in the literature.
Keywords: P00; P16; D02; E02; N2; 330; institutional shocks; natural experiment; share prices; Chile; socialism; military coup; elections